The gene II proteins of the filamentous phages IKe and Ff (M13, fd and f1) are not functionally interchangeable during viral strand replication. - Peeters, B P (1986)
Gene II protein is the only phage-encoded protein required for the double-stranded DNA replication of the distantly related filamentous phages IKe and Ff (M13, fd and f1). Complementation studies have demonstrated that, despite a significant degree of homology between the nucleotide sequences of the gene II's of IKe and Ff and the core's (domains A) of their viral strand replication origins, the biological functions of the gene II proteins are not interchangeable. The specificity of these proteins is not determined by the nucleotide sequence (domain B) which is required for efficient initiation of viral strand replication of Ff. In fact, our data indicate that a sequence with a similar function as domain B in Ff does not form part of the viral strand replication origin of IKe.